Instagram as a pedagogical tool in pediatric dentistry and ortodontic courses = Instagram como herramienta pedagógica en cursos de odontopediatría y ortodoncia - Gutiérrez Marín, Natalia 1975-
Social networks have become an ideal space for the exchange of information and knowledge. The objetive of this study was to determine the usefulness of the implementation of Instagram as a didactic tool to promote and facilitate student learning in the theoretical and laboratory courses of Pediatric Dentistry and Orthodontics during 2022. Private Instagram accounts were created for each of the four courses. During 4 months relevant information was posted to review concepts and strengthen the teaching-learning process of the students. At the end of the courses, a survey was conducted containing the following variables: usefulness of the social network, amount of information provided, preferred place to view content (wall or stories) and whether students recommend the use of Instagram in other courses of the Department of Dentistry and Orthodontics. For the association of variables, the chi-square test was used, value of p<0.05, 95%Cl. The participation in the accounts was 222 individuals; the interaction of the students with the accounts was 87.5% with respect to the stories, 95% observed the stories completely. There was a statistically significant difference with respect to where the information was posted: stories was the preferred place for students. There were 167 students participating in the survey. All the students found very useful or useful the content of the application on the social network.100% of the respondents recommended keeping the implementation of social networks in the theoretical courses of the Department. Instagram is not only a social application but also a channel to make the teaching process more dynamic and attractive. Teachers can integrate this social platform to foster motivation and learning in students.